Pro Android Wearables Building Apps for Smartwatches - Jackson, Wallace (Apress : Imprint: Apress, 2015)
Pro Android Wearables details how to design and build Android Wear apps for new and unique Android wearable device types, such as Google Android smartwatches, which use the new WatchFaces API, as well as health-monitoring features and other cool features such as altimeters and compasses. It's time to take your Android 5 Wear application development skills and experience to the next level and get exposure to a whole new world of hardware. As smartwatches continue to grab major IoT headlines, there is a growing interest in building Android apps that run on these wearables, which are now being offered by dozens of major manufacturers. This means more revenue earning opportunity for today's indie app developers. Additionally, this book provides new media design concepts which relate to using media assets, as well as how to optimize Wear applications for low-power, single-core, dual-core or quad-core CPUs, and how to use the IntelliJ Android Studio IDE, and the Android device emulators for popular new wearable devices.